Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1093/ibd/izab083
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Cognitive-Behavioral and Mindfulness-Based Stress Reduction on the Quality of Life of Patients With Crohn Disease

Abstract: Background Patients with Crohn disease have debilitating psychological symptoms, mental fatigue, and poor quality of life. Psychological intervention may improve these symptoms. Methods We performed a randomized parallel-group physician-blinded trial of cognitive-behavioral and mindfulness-based stress reduction (COBMINDEX) on quality of life and psychological symptoms in adults with mild-moderate Crohn disease. COBMINDEX was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 45 publications
2
38
0
1
Order By: Relevance
“…The two main components of the intervention were (a) guided group discussions, and (b) learning and practicing CBT techniques and skills (e.g., breathing, guided imagery of a 'safe place', constructing positive self-talk, mindfulness meditations, and more) aimed at identifying non-adaptive cognitive schemes and developing capacities to promote better coping. The collection of therapeutic techniques in our intervention protocol is based on recent evidence indicating that combined mindfulness-CBT programs were found effective in assisting people to cope with a variety of health conditions such as anxiety [37], insomnia [38], and Crohn's disease [39].…”
Section: Interventionmentioning
confidence: 99%
“…The two main components of the intervention were (a) guided group discussions, and (b) learning and practicing CBT techniques and skills (e.g., breathing, guided imagery of a 'safe place', constructing positive self-talk, mindfulness meditations, and more) aimed at identifying non-adaptive cognitive schemes and developing capacities to promote better coping. The collection of therapeutic techniques in our intervention protocol is based on recent evidence indicating that combined mindfulness-CBT programs were found effective in assisting people to cope with a variety of health conditions such as anxiety [37], insomnia [38], and Crohn's disease [39].…”
Section: Interventionmentioning
confidence: 99%
“…Therefore, the authors concluded that COBMINDEX has improved patients quality of life and reduced psychiatric symptoms and fatigue. Actually, patients with severe early psychological symptoms most benefited from COBMINDEX [ 198 ].…”
Section: Infection and Autoimmunity During Auto13mentioning
confidence: 99%
“…Mindfulness-based therapies have a modest effect in IBD on QOL, stress and depression but have no effect on anxiety 54 55. CBT can be combined with mindfulness and in one recent randomised controlled trial (RCT) was shown to reduce psychological symptoms and fatigue in patients with mild-to-moderate Crohn’s disease 56…”
Section: Stepped Care For the Recognition And Management Of Psycholog...mentioning
confidence: 99%